Factors influencing disability inclusion practice on social media - Chan, Joye Wai Peng; Phillips, Jenny O.L. (Proceedings of the 2023 14th International Conference on E-business, Management and Economics, 2023)
Digital inclusion in Macao is in the very beginning stage, and disability inclusion practice on social media in producing and promoting accessible social media content and needs is hard to find. This study aims to analyse the factors that influence communication staff's practice of disability inclusion on social media by using the combined employee behaviour and communication process model to provide suggestions to management who wants to promote disability inclusion practice on social media.The Service Centre for the Deaf of the Macau Deaf Association (MDA) was selected as the object for this case study. The online social media used for MDA's communication was analysed, and semi-structured in-depth interviews with members of the Association were conducted. The research findings showed that, except for the reward structure, factors examined from the work environment in terms of organisation, supervision and co-workers; communication staff themselves; outcomes of accessible social media communication; audience and feedbacks show relations with disability inclusion practices on social media. The delivery of inclusive culture, the influential power of disability stakeholders and the positioning of social media platforms are the key influencing factors.The interesting part of this study is that people without disabilities seem to be excluded from the disability inclusion practice carried out on MDA's Facebook. Their social media content is highly accessible to deaf and hard-of-hearing audiences yet seems not to involve the general public. The study object is a good model for producing accessible content, yet the optimisation of promoting social media accessibility needs further exploration.
Keywords: Accessible Social Media (ASM); Disability Employment; Disability Inclusion; Macau Deaf Association

Sustainable Buildings’ Projects – A Perspective from Consultants and Contractors based in Macau SAR, China - J.P.P. Santos, Eduardo; Lobo Marques, Joao; Phyllips, Jenny O. L. (The 2021 12th International Conference on E-business, Management and Economics, 2021)
China growing awareness of sustainability has brought out relevant aspects to move towards a green environment. Since its subscription in 2016, China has been committed to implementing the Paris Agreement, and the Greater Bay Area (GBA) development plan prioritizes ecology and pursuing green development. The primary purpose of this research is to perceive the companies' insights concerning the implementation of sustainable buildings’ projects in Macau. For this multi-case study analysis, primary data was gathered from interviews with two groups involved in the construction projects’ lifecycle: Consultants and Contractors, to analyze different perceptions and concerns. The interviews considered two different themes about the main topic: (1) Perception on Companies’ Experience in Sustainable Projects; (2) Key Drivers towards Sustainable Buildings’ Projects’ Implementation. In conclusion, according to the analyzed data, it is essential to notice that companies’ background and the market particularities affect their corporate performance specially connected to the green construction frameworks. The data also indicate that it is necessary to move towards regulations and policies to change corporate and people's mindset.
0 citations (Crossref) [2022-09-21]
Keywords: Construction industry; Green building; Sustainable Policies; Sustainable building

Entrepreneurial Process of SMEs in Macau - Phillips, Jenny O. L.; Oliveira, Nelio (2022 13th International Conference on E-business, Management and Economics, 2022)
In recent years, entrepreneurship and innovation have been highly propagandised for Macau's economic development, diversification, and the Greater Bay Area (GBA). Since 2013, efforts have been exerted by the Macau government to encourage and support entrepreneurship, from the launching of the Young Entrepreneurs' Aid Scheme in 2013 and the Macau Young Entrepreneur Incubation Centre in 2015. While the failure rate of startups has been considered high in most parts of the world, the rate was only as low as 14% in Macau, with many businesses created every year. This research aims to study the unique entrepreneurial environment for small-to-medium enterprises (SMEs) starting up in Macau from the experience of local entrepreneurs who are benefactors of government support. In-depth interviews were conducted to understand the experience and perceptions of these entrepreneurs as they go through each stage of the entrepreneurial process. Existing research on entrepreneurial processes varies from the two-stage process, which focuses on the beginning of an enterprise, to the different models of various stages from ideas generation to exit or long-term development. From the consolidation of the literature on the entrepreneurial process, five key stages were taken to guide this qualitative research. Findings suggested that idea validation at the start of the entrepreneurial process is almost non-existent amongst our research subjects. Yet it does not affect the implementation and growth of these SMEs. The growth strategies tend to be steady and for the long term, with most SMEs having no consideration of an exit plan.
0 citations (Crossref) [2023-03-15]
Keywords: Economic diversification; Entrepreneurial process; Government entrepreneurship aids